Concurrent strengthening of ultrafine-grained age-hardenable Al-Mg alloy by means of high-pressure torsion and spinodal decomposition. (1st June 2017) - Tang, Yongpeng; Goto, Wataru; Hirosawa, Shoichi; Horita, Zenji; Lee, Seungwon; Matsuda, Kenji; Terada, Daisuke
Abstract: In this study, the age-hardening behavior and precipitate microstructures of severely-deformed and then artificially-aged Al-13.4 wt%Mg alloy has been investigated by Vickers hardness test, X-ray diffraction (XRD) analysis, transmission electron microscopy (TEM) and atom probe tomography (APT). The combined processing of high-pressure torsion (HPT) and aging treatment at a temperature below spinodal lines results in a higher attained hardness of ∼HV296 with an age-hardenability (i.e ΔHV31 ± 2) comparable to that of the undeformed specimen without HPT (i.e. ΔHV33 ± 2). The corresponding TEM microstructures consist of modulated structures associated with spinodal decomposition, and quantitative estimation of the amplitude, as well as the wavelength, of Mg fluctuations was successfully conducted by APT for the first time for this alloy system. The linear relationship between the increment of Vickers hardness and the estimated amplitude of the undeformed specimen supposed that Kato's spinodal-hardening mechanism works even in the HPTed specimen with a high number density of grain boundaries. Therefore, our proposed strategy; i.e. taking advantage of spinodal decomposition, is regarded as a convincing approach to achieving concurrent strengthening by ultrafine-grained and precipitation hardenings for the alloys that decompose via spinodal decomposition. Graphical abstract: Image 1